Thymic carcinoma: a cohort study of patients from the European society of thoracic surgeons database - Ruffini, Enrico; Detterbeck, Frank; Van Raemdonck, Dirk; Rocco, Gaetano; Thomas, Pascal; Weder, Walter; Brunelli, Alessandro; Guerrera, Francesco; Keshavjee, Shaf; Altorki, Nasser; Schützner, Jan; Arame, Alex; et al. (Journal of thoracic oncology, 2014)
INTRODUCTION: Thymic carcinoma is a rare and aggressive thymic neoplasm. The European Society of Thoracic Surgeons developed a retrospective database collecting patients undergoing resection for thymic tumors from 1990 to 2010. METHODS: Of 2265 patients with thymic tumors, there were 229 thymic carcinomas. Clinicopathological characteristics were analyzed including age, associated paraneoplastic diseases, stage (Masaoka-Koga), World Health Organization histologic subtypes, type of resection (total/subtotal/biopsy/no resection), tumor size, pre/postoperative treatments, and recurrence. Outcome measures included overall survival (OS), freedom from recurrence, and cumulative incidence of recurrence. RESULTS: A complete resection was achieved in 140 patients (69%). Recurrence occurred in 54 patients (28%). Five- and 10-year OS rates were 0.61 and 0.37. Five- and 10-year freedom from recurrence rates were 0.60 and 0.43. Cumulative incidence of recurrence was 0.21 (3 yr), 0.27 (5 yr), and 0.32 (10 yr). Survival was better after surgical resection versus biopsy/no resection (p < 0.001), after complete resection versus subtotal resection (p < 0.001), and when using Masaoka-Koga system (stages I-II versus III versus IV) (p < 0.001). The use of multidisciplinary treatments resulted in a survival advantage which was significant in the surgery + radiotherapy group (p = 0.02). Incomplete resection (p < 0.0001) and advanced stage (Masaoka-Koga III-IV) (p = 0.02) had a negative impact on OS at multivariable analysis. Administration of adjuvant radiotherapy was beneficial in increasing OS (p = 0.02). CONCLUSIONS: The results of our study indicate that patients with thymic carcinoma should undertake surgical resection whenever possible; a complete resection and early Masaoka-Koga stage are independent predictors of improved survival; our results also suggest that postoperative radiotherapy is beneficial in improving survival.
Keywords: senioři; Thymus Neoplasms; Societies, Medical; spinocelulární karcinom; senioři nad 80 let; Retrospective Studies; Europe; Prognosis; Evropa; Middle Aged; mužské pohlaví; Neoplasm Recurrence, Local; společnosti lékařské; míra přežití; mladý dospělý; Adult; lokální recidiva nádoru; Thymoma; databáze faktografické; Follow-Up Studies; následné studie; Aged, 80 and over; Neoplasm Staging; Young Adult; nádory brzlíku; ženské pohlaví; prognóza; retrospektivní studie; Humans; Survival Rate; lidé středního věku; staging nádorů; dospělí; thymom; Carcinoma, Squamous Cell; Female; Aged; Databases, Factual; lidé; Male